2016
DOI: 10.1007/s10897-016-9989-y
|View full text |Cite
|
Sign up to set email alerts
|

Men's Knowledge About Maternal Serum Screening for Down Syndrome and their Attitude Towards Amniocentesis

Abstract: The present study aimed to assess (i) the impact of screening consultation on male partner's knowledge about second trimester maternal serum screening for Down syndrome and on their attitudes toward amniocentesis, and (ii) the concomitant effect of men's involvement in pregnancy on both knowledge and attitudes. The study included 164 men who accompanied their partners to the screening appointment. Knowledge Questionnaire and Partner's Involvement in Pregnancy Scale with two dimensions, support and distance, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Participants in this study expressed the importance of having the chance to consider the impact of engaging in prenatal genetic testing on the pregnancy and, ultimately, their lives if the decision was made to continue or end a pregnancy identified with a fetal anomaly. This trend is similar to that seen for decisions about the use of conventional serum screens (Wätterbjörk et al, 2015;Williams et al, 2011), chorionic villus sampling, or amniocentesis (Brajenović-Milić & Dorčić, 2017;Werner-Lin et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
“…Participants in this study expressed the importance of having the chance to consider the impact of engaging in prenatal genetic testing on the pregnancy and, ultimately, their lives if the decision was made to continue or end a pregnancy identified with a fetal anomaly. This trend is similar to that seen for decisions about the use of conventional serum screens (Wätterbjörk et al, 2015;Williams et al, 2011), chorionic villus sampling, or amniocentesis (Brajenović-Milić & Dorčić, 2017;Werner-Lin et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
“…Overall fathers suggested that they felt neglected in their interactions with health professionals and would have benefitted from greater efforts to include them. This would support the call for changes to female-orientated prenatal and postnatal services (Brajenović-Milić and Dorčić 2016).…”
Section: Basic Theme: Reactions Of Health Professionals To Their Childmentioning
confidence: 54%